Bounded Community: Designing and facilitating learning communities in formal courses - Wilson, Brent G.; Ludwig-Hardman, Stacey; Thornam, Christine L.; Dunlap, Joanna C. (International Review of Research in Open and Distributed Learning, 2004)
Learning communities can emerge spontaneously when people find common learning goals and pursue projects and tasks together in pursuit of those goals. Bounded learning communities (BLCs) are groups that form within a structured teaching or training setting, typically a course. Unlike spontaneous communities, BLCs develop in direct response to guidance provided by an instructor, supported by a cumulative resource base. This article presents strategies that help learning communities develop within bounded frameworks, particularly online environments. Seven distinguishing features of learning communities are presented. When developing supports for BLCs, teachers should consider their developmental arc, from initial acquaintance and trust-building, through project work and skill development, and concluding with wind-down and dissolution of the community. Teachers contribute to BLCs by establishing a sense of teaching presence, including an atmosphere of trust and reciprocal concern. The article concludes with a discussion of assessment issues and the need for continuing research.